Implementasi Metode Enumerasi Implisit Untuk Penyusunan Menu Makanan Berdasarkan Kebutuhan Kalori - Adhie Saputra; Jong Jek Siang; Lucia Dwi Krisnawati (Universitas Kristen Duta Wacana, 2013)
A simple eating disorder can create variety of disease. In this research, a diet menu created based on the needs of nutrition, using implicit enumeration method. The system will produce minimum price diet menu arrangement 3 times a day for a week, yet still fulfill customer’s nutrition need. Implicit Enumeration Method is used to generate the menu with minimum price. More foods used in this calculation, the implicit enumeration utilization become more optimal. For 10 menus were used in the calculation, the node exploration will be 27.3% of the actual solution, whereas for 15 menus were used, the node exploration will be just 10.9%.